2015
DOI: 10.1007/s10237-015-0727-4
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic properties of human cortical bone with osteogenesis imperfecta

Abstract: The heterogeneity of bone shape and size variation is modulated by genetic, mechanical, nutritional, and hormonal patterning throughout its lifetime. Microstructural changes across cross sections are a result of mechanistic optimization that results over the years of evolution while being based on universal, time-invariant ingredients and patterns. Here we report changes across anatomical sections of bone with osteogenesis imperfecta (OI) that undermines the work of evolution through genetic mutation. This wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…At longer‐scale lengths, oim‐/‐ mice demonstrate reduced stable crack extension, crack‐initiation toughness, and crack‐growth toughness with increasing severity of OI and amounts of woven bone; in addition, increased cortical vascular porosity in oim reduces stable crack growth . Although excessive woven bone is not a clear feature in human OI bone biopsies, increased cortical porosity is, and likely also contributes to increased fracture risk . Fig.…”
Section: Energy Dissipation In Bone and Fracture Toughening Mechanismsmentioning
confidence: 95%
See 1 more Smart Citation
“…At longer‐scale lengths, oim‐/‐ mice demonstrate reduced stable crack extension, crack‐initiation toughness, and crack‐growth toughness with increasing severity of OI and amounts of woven bone; in addition, increased cortical vascular porosity in oim reduces stable crack growth . Although excessive woven bone is not a clear feature in human OI bone biopsies, increased cortical porosity is, and likely also contributes to increased fracture risk . Fig.…”
Section: Energy Dissipation In Bone and Fracture Toughening Mechanismsmentioning
confidence: 95%
“…(83,84) Although excessive woven bone is not a clear feature in human OI bone biopsies, increased cortical porosity is, and likely also contributes to increased fracture risk. (85)(86)(87)(88) Fig. 2 summarizes the factors contributing to bone fragility at the different scale lengths.…”
Section: Energy Dissipation In Bone and Fracture Toughening Mechanismsmentioning
confidence: 99%
“…We have also reported that when prostate cancer cells are sequentially cultured with MSCs in these scaffolds, they undergo MET to form multicellular tumoroids that mimic the early colonization stage of prostate cancer bone metastasis . Genetic changes have been shown to be influencing both collagen and mineral in bone diseases such as osteogenesis imperfecta . The excessive and variant genetic changes during prostate cancer bone metastasis are suggestive of changes to the bone at metastasis.…”
Section: Introductionmentioning
confidence: 91%
“…(36)(37)(38) Genetic changes have been shown to be influencing both collagen and mineral in bone diseases such as osteogenesis imperfecta. (39)(40)(41) The excessive and variant genetic changes during prostate cancer bone metastasis are suggestive of changes to the bone at metastasis. Hence, in this study, we investigated the effect of metastasized prostate cancer cells on bone regeneration, degradation, mineralization, and collagen synthesis using two different prostate cancer cell lines: PC-3 and MDA PCa 2b.…”
Section: Introductionmentioning
confidence: 99%
“…A typical three-region shape and hysteresis behavior of a fibril-based constitutive response as well as the transition from a yielding-like to a brittle-like behavior are recovered with a special insight on the underlying nanoscale mechanisms. The last paper in this series examines the microstructure and molecular composition of different anatomical positions in the diaphysis of an osteogenesis imperfecta human tibia (Katti et al 2015). The study shows that although there is no significant microstructural difference, molecular changes are observed using FTIR, revealing differences in molecular composition of the four anatomical positions.…”
mentioning
confidence: 99%